Analisis Preferensi Konsumen Beras Di Kabupaten Bondowoso Indonesia (Studi Kasus Pada Beras â€œPutri Kokiâ€ Produksi PT. Samudra Indo Pangan Bondowoso) - Rizal, Rizal (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the characteristics of rice consumers in Bondowoso and determine which combination of rice attributes is included in consumer preferences. The research method is descriptive analysis and conjoint analysis. The research results show that consumer preferences for rice in Bondowoso are influenced by taste, color, rice grains, packaging and price. The taste of rice that consumers in Bondowoso want is delicious rice. Apart from that, consumers prefer small, clean white packaging and low prices for rice products, which contain information related to rice and the product brand.